Decision-making in bus-transit systems: A comprehensive approach based on stochastic multi-criteria acceptability analysis - Jônatas Augusto Manzolli; Pascal Messier; João Pedro F. Trovão; Carlos Henggeler Antunes (Sustainable Futures)
The shift to sustainable transportation presents challenges regarding the acquisition or replacement of bus fleets. The need to consider multiple, conflicting and incommensurate factors such as environmental impact, cost-effectiveness, and technological issues makes the decision-making process more complex, time-consuming, and possibly ineffective, thus requiring an adequate multi-criteria evaluation framework. To this end, this study employs the stochastic multi-criteria acceptability analysis method, assessing the feasibility of transitioning to eco-friendly bus fleets by comparing diesel, hybrid, and electric buses while addressing uncertainty. Using the bus transportation system of Sherbrooke (Canada) as a case study, computational simulations generate energy consumption data and define bus system configurations. The case study evaluates five concrete alternatives over twelve criteria. The results show that an electric bus system with an overnight charging strategy outperforms other options (in 32 % of the cases) due to its reliability, cost-effectiveness, and mixed use of the bus fleet. Conversely, the diesel bus alternative consistently ranks lowest due to poor performance on economic and environmental criteria.